The Development Method of Making Decision in Choosing Academic Informartion System on the Merger University (Case Study: Telkom University) - Rima Aditya, Bayu; Handoko Wijoyo, Mary (International Journal of Engineering and Technology, 2019)
University merger could be defined as the combination between two or more than two Universities that gathered into one. One step conducted during merger was choosing the decision to choose one of many information system alternatives which was originated from the Merger University. Incorrect decision could have disturbance effect on that academic activities of merger Universities. It was because the initial purpose of using the academic information itself was to add the benefit for academic process. The purpose of this research was to develop a method of making decision in choosing academic information system on the Merger University. The development of method was conducted by adapting the characteristics and problems in the merger Universities with the decision making theories. The result of this research were (1) There were two criteria in the decision choosing of academic information system on the merger Universities which were functionality needs and user acceptance, (2) Process of rank giving or priority conducted by using Analytical Hierarchy Process (AHP) method.(3) The result of method development has been tested and implemented on the research object.
Keywords: Merger University; Making Decision; Academic Information System; and AHP